Avances en las ténicas de reducción de tamaño por clasificación de partículas finas - Ornelas Tabares, Jorge; Schönert, Klaus (My University, 1996)
Comminution is a very ancient technique, corn, and minerals have been milled since some thousends years with: Roller mills, cone mills, buhr mills, stamp mills. The material is stressed between two hard surfaces by compression and shear. Tumbling mills were developed at the beginning of the last century, the material is also stressed by compression and shear between the tumbling bodies.
Keywords: crushers; interparticle; denotations; througput; vibration